WHY PRESIDENT CLINTON'S CIGARETTE TAX PLAN IS UNFAIR TO AMERICA'S SMOKERS (Tufts Archival Research Center, 2007)
Brochure explaining problems associated with a cigarette tax increase. Urges smokers to write Congress, send letters to the editor, and call and visit lawmakers. Lists points to make, including the inadequacy of tax to finance health care, the negative economic impact, the inappropriateness of government in health care, the lack of effect on youth smoking, the regressive nature of taxes, and the bureaucratic waste.